Media Pembelajaran Interaktiv Aksara Jawa Berbasis Multimedia dengan Animasi 2D - Wulan Cahyaningrum; Sri Widiyanti; Lilik Sugiarto (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
Javanese language is local content for levels from elementary to high school, the aim of learning Javanese is an effort to preserve Javanese culture. Therefore, to achieve these learning objectives, interactive learning media is needed according to students' needs. The researcher developed material introducing Javanese script, using animation media which was created with the aim of achieving the expected goals in the learning process. The results of this research are audio and video based which students can use in learning media. With this media, students can easily learn about the Javanese script presented by the teacher, this speeds up understanding of the material presented by the teacher.